2010
DOI: 10.1007/s00520-010-1064-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life in Australian women previously diagnosed with gynaecologic cancer

Abstract: Despite limitations, these data shed light on challenges to QOL of a heterogeneous group of gynaecologic cancer survivors. Sexual and psychological morbidity outcomes compare favourably with the literature while body image disturbance may present a useful target for clinical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…E ndometrial cancer is a common form of gynecologic cancer, originating in the endometrium, the inner lining of the uterus. 9,10 In 2 studies, emotional QoL among women with endometrial cancer was comparable by 5 years after diagnosis to women without cancer, 11 but younger women with endometrial cancer were found to have higher distress than older women either with or without cancer. 2 Quantitative surveys show reduced physical health during endometrial cancer treatment 3 and up to 2 years later 4,5 ; however, by 5 years after treatment, physical health-related quality of life (QoL) appears comparable to general population norms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…E ndometrial cancer is a common form of gynecologic cancer, originating in the endometrium, the inner lining of the uterus. 9,10 In 2 studies, emotional QoL among women with endometrial cancer was comparable by 5 years after diagnosis to women without cancer, 11 but younger women with endometrial cancer were found to have higher distress than older women either with or without cancer. 2 Quantitative surveys show reduced physical health during endometrial cancer treatment 3 and up to 2 years later 4,5 ; however, by 5 years after treatment, physical health-related quality of life (QoL) appears comparable to general population norms.…”
mentioning
confidence: 99%
“…7,8 However, there is little evidence specific to women with endometrial cancer that examines long-term emotional adjustment. Although other quantitative studies of women with gynecologic cancer have also identified aspects of positive change, 10,15 most studies have focused on negative changes. 12 Adjustment to cancer can be complex, and a diagnosis of cancer can lead to both negative and positive physical, emotional, social, and spiritual changes, which may lead to fluctuations in QoL.…”
mentioning
confidence: 99%
“…Although used somewhat frequently in reference to adults who have been treated for cancer, no clear definitions of body image disturbance were found (Anagnostopoulos & Myrgianni , Shoma et al . , Stafford & Judd , Hazewinkel et al . , Kim et al .…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, body image disturbance has been significantly associated with problems with speech and eating (Fingeret et al . ), poorer sexual satisfaction (Stafford & Judd ), severe defecation symptoms (Hazewinkel et al . ) and total gastrectomy as opposed to subtotal gastrectomy (Kim et al .…”
Section: Resultsmentioning
confidence: 99%
“…Data from women previously diagnosed with gynecologic cancer show that 87 % have at least one unmet need and 25-30 % have an unmet need for assistance with worry about cancer recurrence, reducing stress in their lives or concerns about communication in the healthcare team [ 60 ]. It would be unacceptable to deny these individuals access to psychological help on the basis of suffering from serious adjustment problems rather than a psychiatric disorder [ 10 ].…”
Section: Screening For Distress Is Not Effi Cientmentioning
confidence: 98%